Mobile EEG examination of putative biomarkers of mental health in individuals that use cannabis - Conor H. Murray; Kaihan Danesh; Ziva D. Cooper (NPP-Digital Psychiatry and Neuroscience)
Abstract Healthy individuals that use cannabis are at greater risk of developing mental health conditions than those that do not use cannabis. Here, using mobile electroencephalography (EEG) in controlled laboratory settings, we examined two putative biomarkers of mental health across two studies of people who use cannabis (N = 100, 50% male; N = 40, 60% male). We examined associations to cannabis use and mood and assessed the influence of sex and age on the outcomes. Specifically, in the first study, we examined prefrontal broadband power, previously found to be related to healthy neurocognitive development, in relation cannabis use. We also examined left prefrontal alpha power, previously found to be related to anxiety and depression, in relation to Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) scores. In the second study, we examined only left prefrontal alpha power during the cold pressor test (CPT), which elicits a stress response. We found that in the first study, young males (ages 21–23) showed the greatest association between prefrontal broadband power and cannabis use (R = 0.50; p = 0.007), while females showed associations between left prefrontal alpha power and BAI scores (R = 0.61, p = 0.013). In the second study, the CPT increased anxiousness (p < 0.001) but did not affect left prefrontal alpha power. Together, our findings help to characterize these putative biomarkers in individuals that use cannabis, while informing the utility of mobile EEG devices for tracking markers of mental health and wellness outside of laboratory settings.